Homicide and the politics of law reform - Horder, Jeremy (Oxford : Oxford University Press, 2012)
A fascinating study of the law of homicide, examining its recent development and providing an insider's view on the politics of law reform. Challenging current thought, it argues for the general public to have a greater role in the process of law reform including offenses such as murder, manslaughter, and the highly debated corporate homicide.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Homicide; Law reform